Hunter-gatherer archaeology of the Colorado High Country - Stiger, Mark (UPCC book collections on Project MUSE., 2001)
An overview of both past research and significant new findings and interpretations of archaeological work conducted in Colorado's Upper Gunnison Basin, including a massive body of data from the author's eight years of work at the Tenderfoot lithic-scatter site. This important new contribution to archaeology in the southern Rocky Mountains uses an organizational approach to describe and interpret prehistoric cultural change across wide areas of Western Colorado.